2012
DOI: 10.1016/j.celrep.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-C Promotes Immune Tolerance in B16 Melanomas and Cross-Presentation of Tumor Antigen by Lymph Node Lymphatics

Abstract: Tumor expression of the lymphangiogenic factor VEGF-C is correlated with metastasis and poor prognosis, and although VEGF-C enhances transport to the draining lymph node (dLN) and antigen exposure to the adaptive immune system, its role in tumor immunity remains unexplored. Here, we demonstrate that VEGF-C promotes immune tolerance in murine melanoma. In B16 F10 melanomas expressing a foreign antigen (OVA), VEGF-C protected tumors against preexisting antitumor immunity and promoted local deletion of OVA-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
360
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(379 citation statements)
references
References 43 publications
17
360
1
1
Order By: Relevance
“…In concert with primary tumors, our study identifies immune suppressive molecules in tumor-draining LNs, suggesting that immune mechanisms operating in metastatic LNs 25 , 37 , 61 , 62 may at least in part be similar to those in primary tumors. 63 In contrast to primary tumors, we found a significant correlation between LECs and FoxP3 + lymphocytes.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In concert with primary tumors, our study identifies immune suppressive molecules in tumor-draining LNs, suggesting that immune mechanisms operating in metastatic LNs 25 , 37 , 61 , 62 may at least in part be similar to those in primary tumors. 63 In contrast to primary tumors, we found a significant correlation between LECs and FoxP3 + lymphocytes.…”
Section: Discussionmentioning
confidence: 75%
“…38-40 In human melanoma, increased intra- and peritumoral LVD as well as the lymphatic growth factor VEGF-C strongly correlate with metastatic dissemination. 17 , 33 , 41-43 Lymphatic vessels may support migration of tumor cells, but may also modulate immune cells, as recently demonstrated in primary tumors and draining LNs in mice, 24 , 25 , 44 raising the possibility that lymphatics mediate immune suppression and poor clinical outcome in cancer patients. 19 , 31 , 42 Because corresponding human data are missing, we performed a very wide IHC analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Large or opsonized antigens are taken up by subcapsular macrophages, whereas smaller antigens flow into small conduits lined with follicular DCs in which they can be taken up directly by antigen-specific B cells (21). On the other hand, LECs have access to all lymph-borne antigens, and it was recently shown that LECs can actively scavenge these antigens, process them intracellularly, and cross-present them to T cells for deletional tolerance (22,23), which is discussed in more detail later. Furthermore, LECs can retain antigen for long periods of time and may play a role in recalling memory T cells (24).…”
Section: Lymph Flow Of Antigensmentioning
confidence: 99%